2017
DOI: 10.3389/fped.2017.00097
|View full text |Cite|
|
Sign up to set email alerts
|

Epinephrine Use during Newborn Resuscitation

Abstract: Epinephrine use in the delivery room for resuscitation of the newborn is associated with significant morbidity and mortality. Evidence for optimal dose, timing, and route of administration of epinephrine during neonatal resuscitation comes largely from extrapolated adult or animal literature. In this review, we provide the current recommendations for use of epinephrine during neonatal resuscitation and also the evidence behind these recommendations. In addition, we review the current proposed mechanism of acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 75 publications
1
22
0
2
Order By: Relevance
“…Although no studies have examined the optimum timing of adrenaline in the neonatal population, pediatric studies have shown that delay to first adrenaline dose is associated with decreased return of spontaneous circulation and survival (49). Many questions remain to be answered in relation to adrenaline administration (50). Observational studies have shown that in infants requiring adrenaline during resuscitation, only 40% received their first dose within the first 10 min of life, with the median age to first adrenaline dose of 10 min (95% CI 8-14 min) (51).…”
Section: Adrenaline/accessmentioning
confidence: 99%
“…Although no studies have examined the optimum timing of adrenaline in the neonatal population, pediatric studies have shown that delay to first adrenaline dose is associated with decreased return of spontaneous circulation and survival (49). Many questions remain to be answered in relation to adrenaline administration (50). Observational studies have shown that in infants requiring adrenaline during resuscitation, only 40% received their first dose within the first 10 min of life, with the median age to first adrenaline dose of 10 min (95% CI 8-14 min) (51).…”
Section: Adrenaline/accessmentioning
confidence: 99%
“…Further, once CC are given, a vascular access should be established for epinephrine administration 3 . Other than increasing the heart rate, heart contractility, and myocardial relaxation rate via stimulating β-receptors, epinephrine has also been shown to cause vasoconstriction of both peripheral and coronary arteries by activating α-receptors (3,4). However, both the effectiveness and safety for using epinephrine during resuscitation are still debatable (3)(4)(5).…”
mentioning
confidence: 99%
“…We followed a protocol and were able to reproduce severe asphyxia with very similar degrees of acidosis and hypoxemia in both study groups, confirming that this model is quite stable. We followed closely the published resuscitation guidelines and used epinephrine before volume expansion and all animals received at least one dose of epinephrine, which, because of its positive effect on coronary blood flow, is considered to be important for successful resuscitation ( 24 ). Volume depletion was approximately 1/3 of the estimated blood volume.…”
Section: Discussionmentioning
confidence: 99%